2019
DOI: 10.4103/jmau.jmau_10_19
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of myofibroblasts using alpha-smooth muscle actin (SMA) to assess the aggressive potential of various clinical subtypes of ameloblastoma

Abstract: Objective:Ameloblastoma is a rare odontogenic neoplasm with high recurrence rates if improperly treated. If left untreated (or is treated inadequately), it can cause substantial morbidity, disfigurement, and even death. Hence, there is a need to explore the stromal cells too, which might play an important role in assessing its aggressive behavior and may help to predict the recurrence of different clinical variants of ameloblastoma. Myofibroblasts (MFs) are such cells which have been studied in various lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Immunohistochemical staining of all samples was performed using anti-alpha-smooth muscle actin (SMA) antibody (Agilent Technologies, Santa Clara, CA, USA). The staining protocol was performed essentially as described previously ( Mudaliar et al, 2019 ). The number of myofibroblasts in the corneal stroma per HPF was calculated following staining for SMA.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining of all samples was performed using anti-alpha-smooth muscle actin (SMA) antibody (Agilent Technologies, Santa Clara, CA, USA). The staining protocol was performed essentially as described previously ( Mudaliar et al, 2019 ). The number of myofibroblasts in the corneal stroma per HPF was calculated following staining for SMA.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that ameloblastoma showed the highest number of myofibroblasts compared with dentigerous cysts and odontogenic keratocysts [ 87 ]. Mudaliar et al [ 88 ] also found that solid/multicystic ameloblastoma contain more myofibroblasts in the stroma than unicystic ameloblastoma. Myofibroblasts are variants of fibroblasts that express α-SMA; are found in both fibroblasts and smooth muscle cells; and secrete cytokines, growth factors, and abundant extracellular matrix [ 89 ].…”
Section: The Role Of Stromal Components In Ameloblastomamentioning
confidence: 99%